Blue whales off the Southern coast of Sri Lanka during the Southwest Monsoon Season - Russell, Grace; Bridge, Marcus; Nimak-Wood, Maja (The journal of cetacean research and management, 2020)
Observations of 37 individual blue whales (Balaenoptera musculus) were recorded off the southern coast of Sri Lanka during the Southwest Monsoon Season (SWM). Sightings were made during a scientific geophysical survey campaign conducted in July and August 2017. Whilst blue whales are regularly recorded on the continental slope of southern Sri Lanka during the Northeast Monsoon Season (NEM) (December - March) and during the two inter-monsoonal periods (March - April and September - October), limited data is available for the SWM (May - September) mostly due to unfavourable weather conditions and very little survey effort. In the northern hemisphere blue whales undertake seasonal migrations from higher latitude feeding grounds to lower latitude breeding and wintering areas. However it has been suggested that a population of blue whales in the Northern India Ocean (NIO) remains in lower latitudes year round taking advantage of the rich upwelling areas off Somalia, southwest Arabia and western Sri Lanka. Data from this study nevertheless support a theory that a certain number of individuals remain off the southern coast off Sri Lanka during the SWM, suggesting that the productivity in this region is sufficient to support their year-round presence. This study therefore fills a knowledge gap regarding the presence and movement of blue whales in the NIO highlighting the importance of data obtained from platforms of opportunity.